Simultaneous determination of naltrexone and bupropion in their co-formulated tablet utilizing green chromatographic approach with application to human urine - Sherif A. Abdel-Gawad; Rania M. El-Gamal (Elsevier, 2018)
A rapid, simple and accurate micellar HPLC-method was adopted and validated for concurrent quantification of naltrexone hydrochloride (NTX) and bupropion hydrochloride (BUP). The proposed method was conducted on RP-18 LiChrosorb® column (150 mm × 4.6 mm i.d. 5-µm particle size) at 25 °C, as a stationary phase and a mixture of 0.175 M sodium dodecyl sulphate (SDS), 0.3% triethanolamine (TEA) and 12% n-propanol in 0.02 M ortho (o)-phosphoric acid of pH 3.5 as a developing system. It was pumped at a flow rate of 1.2 mL/min, with ultraviolet detection at 210 nm. The linearity ranges were 0.5-15.0 µg/mL and 1.2-18.0 µg/mL, with detection limits of 0.10 and 0.31 µg/mL and quantification limits of 0.30 and 0.93 µg/mL for NTX and BUP, respectively. The studied drugs were successfully quantified by applying the proposed method in their co-formulated tablet. The cited method was also applied for in-vitro quantification of BUP in spiked human urine without prior extraction.